Addicted to Power: Sexual Harassment and the Unethical Behaviour of University Faculty - Carr, Rey A. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper examines sexual harassment as a form of unethical behaviour in universities. The author argues that codes of ethics and guidelines for sexual harassment do not address the foundation of sexual harassment, namely, the imbalance of power in the university. The university workplace is depicted as an oasis for persons addicted to power and an addictions framework is employed to explain and describe how power addicts become involved in sexual harassment. Colleagues and administrators are seen as enabling sexual harassment through co-dependency, denial, impression management, historical distortion, resistance to self-study, and confusing confidentiality with secrecy. Attempts to perfect harassment guideline language as well as other university obsessions are seen as symptoms of an addicted organization. Faculties teaching in clinically oriented university degree programs, particularly at the graduate level, are described as being at risk because of their dual relationships with students. Training for administrators in constructive confrontation and progressive discipline techniques, peer-based employee assistance programs, equity procedures, positive milieu groups, clarity of role boundaries, and a new paradigm for university organization are suggested as appropriate interventions. Examples taken from actual case studies are used to illustrate various points.